2013
DOI: 10.1111/jonm.12028
|View full text |Cite
|
Sign up to set email alerts
|

Workplace empowerment and nurses' job satisfaction: a systematic literature review

Abstract: This review could be useful for guiding leaders' strategies to develop and maintain an empowering work environment that enhances job satisfaction. This could lead to nurse retention and positive organisational and patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
204
0
37

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(248 citation statements)
references
References 62 publications
7
204
0
37
Order By: Relevance
“…11,12,[36][37][38] The AACN CSI Academy and participating hospitals provided these structures based on evidence that structural and psychological empowerment boosts job satisfaction and decreases job strain. 38 This type of staff empowerment to lead planning efforts that improve clinical outcomes has not become the industry standard, although it is required for successful implementation. 39 Top-performing hospitals believe excellent process and patient outcomes are driven by engaged employees with input from frontline staff.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,[36][37][38] The AACN CSI Academy and participating hospitals provided these structures based on evidence that structural and psychological empowerment boosts job satisfaction and decreases job strain. 38 This type of staff empowerment to lead planning efforts that improve clinical outcomes has not become the industry standard, although it is required for successful implementation. 39 Top-performing hospitals believe excellent process and patient outcomes are driven by engaged employees with input from frontline staff.…”
Section: Discussionmentioning
confidence: 99%
“…Diversos estudios han mostrado que el empowerment psicológico se relaciona con una mayor satisfacción de los empleados, un elevado compromiso con la empresa y una mayor productividad (Cicolini et al, 2013;Seibert, Wang & Courtright, 2011;Spreitzer, Kizilos & Nason, 1997;Zhou, Wang, Chen & Shi, 2012). Relativamente a la relación entre el empowerment psicológico y la satisfacción laboral, se han observado correlaciones positivas y significativas en diversos países y muestras: en personal médico (Cicolini et al, 2013), vendedores de textiles (Erdogan & Bauer, 2009) o trabajadores de empresas petroquí micas (Yao, 2013).…”
Section: Empowerment Psicológico En El Trabajounclassified
“…Relativamente a la relación entre el empowerment psicológico y la satisfacción laboral, se han observado correlaciones positivas y significativas en diversos países y muestras: en personal médico (Cicolini et al, 2013), vendedores de textiles (Erdogan & Bauer, 2009) o trabajadores de empresas petroquí micas (Yao, 2013). En general, se asume que cuando los trabajadores perciben que tienen autonomía y competencia para realizar tareas con significado y un elevado impacto en la organización, se sienten más satisfechos en sus puestos (Seibert et al, 2011).…”
Section: Empowerment Psicológico En El Trabajounclassified
“…[69][70][71][72][73][74] A majority of participants thought nurses should have more power and input into decisions about their working conditions. Other research [75,76] focusing on empowerment has found that when nurses feel they have some control and power, they provide better care and have higher job satisfaction. Further, participants wanted nurses who have a long experience in patient care to have more influence in health policy and patient advocacy.…”
Section: Findings' Relation To Other Studiesmentioning
confidence: 99%